RESOLUSI KEMISKINAN RUMAH TANGGA NELAYAN DI NEGERI SEILALE - Mariwy, Susi Maria; Therik, Wilson M.A. (Universitas Kristen Satya Wacana, 2020)
Fishermen's household poverty is something that should not be underestimated because of its abundant natural products, but they are still under the cycle of poverty. A household is said to be poor if it is not able to meet the needs of their lives. Household economic characteristics are an important part of family or community life in general. Economic characteristics arise because of the desire to act in a situation that is possible with the aim of obtaining benefits for the family. Which aims to understand the household life of fishermen in the State of Seilale. In this research, data collection was done by interview, observation and documentation study using an exploratory approach. The poverty problem that occurs in Seilale fishing households is inseparable from various causes of poverty. The factors that cause poverty in the form of changes in catching season, this factor has caused uncertainty of the catches of the fishermen, so that when the season is not catching fish the fishermen find it very difficult to meet their daily consumption needs. Low education, low expertise makes fishermen stay afloat to become a traditional fisherman. Fishing equipment that is still simple and inadequate makes them also have to compete with fishermen who have modern equipment.